Development, construct validity and test–retest reliability of a field-based wheelchair mobility performance test for wheelchair basketball. Issue 1 (2nd January 2018) - de Witte, Annemarie M. H.; Hoozemans, Marco J. M.; Berger, Monique A. M.; van der Slikke, Rienk M. A.; van der Woude, Lucas H. V.; Veeger, Dirkjan (H. E. J)
ABSTRACT: The aim of this study was to develop and describe a wheelchair mobility performance test in wheelchair basketball and to assess its construct validity and reliability. To mimic mobility performance of wheelchair basketball matches in a standardised manner, a test was designed based on observation of wheelchair basketball matches and expert judgement. Forty-six players performed the test to determine its validity and 23 players performed the test twice for reliability. Independent-samples t- tests were used to assess whether the times needed to complete the test were different for classifications, playing standards and sex. Intraclass correlation coefficients (ICC) were calculated to quantify reliability of performance times. Males performed better than females ( P < 0.001, effect size [ES] = −1.26) and international men performed better than national men ( P < 0.001, ES = −1.62). Performance time of low (≤2.5) and high (≥3.0) classification players was borderline not significant with a moderate ES ( P = 0.06, ES = 0.58). The reliability was excellent for overall performance time (ICC = 0.95). These results show that the test can be used as a standardised mobility performance test to validly and reliably assess the capacity in mobility performance of elite wheelchair basketball athletes. Furthermore, the described methodology of development is recommended for use in other sports to develop sport-specific tests.